PENGARUH PELATIHAN KERJA, KOMPETENSI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DI BANK ACEH SYARIAH BANDA ACEH - Dewi, Nurmala; Zuswana, Aries (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the influence of Job Training and Competency on Employee Performance, as well as the role of Work Motivation as a mediating variable in Bank Aceh Syariah. Employee performance is a key factor in increasing a company's productivity and competitiveness, so it's important to know the factors that affect it. The approach used in this study is quantitative with the Structural Equation Modeling–Partial Least Square (SEM-PLS) method to analyze the relationships between variables. The number of samples used was 122 respondents, who were active employees with in Bank Aceh Syariah. The results of the study show that Competence has a positive and significant effect on Employee Performance and Work Motivation. Work Motivation has also been proven to have a significant effect on Employee Performance. Meanwhile, Job Training has a significant effect on Work Motivation, but does not have a direct effect on Employee Performance. The mediation analysis showed that Work Motivation was able to mediate the influence of Competency on Employee Performance, but did not mediate the influence of Job Training on Employee Performance. This study concludes that improving employee competence and work motivation is a strategic step in encouraging optimal performance. Therefore, Bank Aceh Syariah is advised to continue to develop a structured human resource development program that is structured, measurable, and oriented towards increasing employee motivation and competence in a sustainable manner.